Improving Learning Outcomes through Problem-Based Learning with PQ4R Method - Herlina Herlina; Sunarlia Sunarlia (USN Kolaka, 2020)
The purpose of this research is to improve mathematics learning outcomes on line and angle material. This research including Quasi Experiments using True Experimental Design with Posttest-Only Control design. The subject of this research is a class VII student of MTs Swasta Tontonunu in the year 2017 which consists of the 2 classes each as class experiment and class control. The instrument used is a test instrument, sheet observation activity students, and sheets observation teacher activity in learning. Data analysis used the difference of two mean, namely the t-test of two independent samples was good assumption variance same or no, but previously tested the normal distribution using Kolmogorof Sminov. The results of the descriptive analysis showed that the mean posttest class experiment 78.76 19 higher than the mean posttest class control 73, 375. The results of the two- way difference test on mean show a significance value (2 tailed) 0.005< (0.05) which means that the mean of the two posttests issignificantly different. Based on the results of the study, it was concluded that the application of the learning model based on problem with PQ4R method can improve learning outcomes math on the subject discussion of lines and angles. This is possible because of learning based on problem started with introduce real everyday problems will more meaningful and moreeasy recognized by students. And through PQ4R, material on the subject discussion of lines and angles more many about fact will moreeasy understood in accordance steps preview, question, read, reflect, recite, and review.